PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN (STUDI KASUS PADA PDAM TIRTA MOEDAL KOTA SEMARANG) - Erina Try Anindya; Hesti Lestari; , Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro)
The reason behind this research is based on numerous complaints from the public regarding dissatisfaction with the quality of service and price set by PDAM Tirta Moedal Semarang. The purposes of this research are: (1) To know the effect of PDAM Tirta Moedal Semarang’s service quality on customer satisfaction. (2) To know the effect of PDAM Tirta Moedal Semarang’s set price on customer satisfaction. (3) To know the effect of PDAM Tirta Moedal Semarang’s service quality and set price on customer satisfaction. This research use explanatory quantitative method with 100 research sample. The sampling technique used is Probability Sampling technique. The analysis technique used in this research is Validity Test, Reliability Test, Kendall’s concordance coefficient (W), Kendall Tau’s correlation, and Coefficient of Determination. The results showed that (1) The effect of service quality on customer satisfaction has a 0,545 correlation coefficient with a significance level of 0,01; (2) The effect of price on customer satisfaction has 0,563 correlation coefficient with a significance level of 0,01; (3) The effect of service quality and price on customer satisfaction has 0,998 correlation coefficient with a significance level of 0,01. Based on these results it can be concluded that there is an impact between service quality, price, and between service quality and set price on customer satisfaction at PDAM Tirta Moedal Semarang. The suggestion towards the problem is to make an operational step to improve the quality of service accordance to customer expectations, it is also recommended to develop water quality, and provide clarity on price rates in the customer's water bill.